Pete the Cat. Too cool for school - Dean, Kim, 1969- (Pete the cat., 2014)
"Pete just can't decide which outfit to wear to school! He has so many options to choose from. Fans of Pete the Cat will enjoy Pete's creativity in choosing the coolest outfit" --